Cluster como estrat??gia competitiva para a ind??stria vin??cola : an??lise da competitividade por meio de campos e armas da competi????o - Oliveira, Ivaldir Vaz de (2004)
The aim of this paper is to establish the effect or conseguence of the existence of a cluster (competitive agglomerate) in the competition present in small and medium wine-producing companies. The research field has confirmed the substantive hypothesis: the election of the competition fields and weapons, and the existence of a weapons alignement in the competition field, increases the degree of competitiveness in the company that belongs to the wine cluster of S??o Roque. The evoluation of the enterprise competitiviness has been made by a percentage variation of the production volume from 1998 to 2002, according to information obtained from the corresponding enterprises. The competition fields in the companies, where they try to obtain competitive advantages and the intensity of the compatition weapons they use, was investigated through a questionnaire. The substantive hypothesis was confirmed by the following quantitative variable of the field model and competion weapons: degree of competitiveness of the company, intensity of the company weapons, focus and diffusion. The variables were tested statistically by the Student Test and Pearson Correlation. The results of the research accomplished in the wine-producing enterprises of S??o Roque contributed in a scientifically way to the Competitiveness Theory, because: 1. they have showed one more evidence ofthe validity of the model fields and competition weapons ??? for an enterprise to be competitive, it???s enough to have excellence only in that little weapons that give competitive advantage in the field that was chosen to compete; 2 - they have also showed that the strategy formulation can summarize the competition field choice, what facilitates the methodology formulation strategy. 3. they have validated the quantitative methodology of field models and competition weapons, based on the variable mentioned above; 4 ??? they have confirmed that the field model and competition weapons are enough to analyse, explain and increase the competitiveness of a company or a group of companies.